2018
DOI: 10.1016/j.ajhg.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Missense Variants in RHOBTB2 Cause a Developmental and Epileptic Encephalopathy in Humans, and Altered Levels Cause Neurological Defects in Drosophila

Abstract: Although the role of typical Rho GTPases and other Rho-linked proteins in synaptic plasticity and cognitive function and dysfunction is widely acknowledged, the role of atypical Rho GTPases (such as RHOBTB2) in neurodevelopment has barely been characterized. We have now identified de novo missense variants clustering in the BTB-domain-encoding region of RHOBTB2 in ten individuals with a similar phenotype, including early-onset epilepsy, severe intellectual disability, postnatal microcephaly, and movement disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 61 publications
5
61
0
Order By: Relevance
“…RHOBTB2 mRNA levels are relatively high in mouse and human neuronal tissues, indicating possible roles in the nervous system (Ramos, Khademi, Somesh, & Rivero, ; St‐Pierre, Jiang, Egan, & Zacksenhaus, ). Consistent with this hypothesis, de novo missense variants in RHOBTB2 were very recently reported in 10 patients with EE (Straub et al., ). Transiently expressed mutant RHOBTB2 was more abundant than wild‐type RHOBTB2, probably because of impaired degradation in the proteasome, indicating that precise regulation of RHOBTB2 levels is essential for normal brain function (Straub et al., ).…”
Section: Clinical Features Of Individuals With De Novo Rhobtb2 Variantssupporting
confidence: 63%
See 1 more Smart Citation
“…RHOBTB2 mRNA levels are relatively high in mouse and human neuronal tissues, indicating possible roles in the nervous system (Ramos, Khademi, Somesh, & Rivero, ; St‐Pierre, Jiang, Egan, & Zacksenhaus, ). Consistent with this hypothesis, de novo missense variants in RHOBTB2 were very recently reported in 10 patients with EE (Straub et al., ). Transiently expressed mutant RHOBTB2 was more abundant than wild‐type RHOBTB2, probably because of impaired degradation in the proteasome, indicating that precise regulation of RHOBTB2 levels is essential for normal brain function (Straub et al., ).…”
Section: Clinical Features Of Individuals With De Novo Rhobtb2 Variantssupporting
confidence: 63%
“…Consistent with this hypothesis, de novo missense variants in RHOBTB2 were very recently reported in 10 patients with EE (Straub et al., ). Transiently expressed mutant RHOBTB2 was more abundant than wild‐type RHOBTB2, probably because of impaired degradation in the proteasome, indicating that precise regulation of RHOBTB2 levels is essential for normal brain function (Straub et al., ).…”
Section: Clinical Features Of Individuals With De Novo Rhobtb2 Variantssupporting
confidence: 63%
“…Most patients presented with neonatal onset encephalopathies and most frequently had variants in KCNQ2 (n = 8) and SCN2A (n = 4). In nine patients, we identified variants in recently described genes such as GNAO1 , NPRL3 , NR2F1, and RHOBTB2 . These variants were not identified or reported clinically because of the time lag between research discovery and clinical testing incorporating new genes.…”
Section: Discussionmentioning
confidence: 99%
“…In nine patients, we identified variants in recently described genes such as GNAO1, 29 NPRL3, [30][31][32] NR2F1, 33 and RHOBTB2. 34 These variants were not identified or reported clinically because of the time lag between research discovery and clinical testing incorporating new genes. Recently, we have observed that some testing laboratories report candidate gene findings, which would make such findings available for assessment and correlation with the clinical phenotype.…”
Section: The Dynamic Landscape Of the Genetic Epilepsiesmentioning
confidence: 99%
“…Analysis of type 1b neuromuscular junctions (NMJs) of muscle 4 was performed as previously described 60 . Male L3 non-GFP larvae upon pan-neuronal manipulation (elav-GAL4/CyO-GFP;elav-GAL4) were dissected in PBST, fixated in 4% paraformaldehyde and stained with nc82 and anti-discs large antibodies (both from the Developmental Studies Hybridoma Bank, Iowa City, IA).…”
Section: Analysis Of Neuromuscular Junctions (Nmjs) From L3 Larvaementioning
confidence: 99%